Efektivitas Penggunaan Kuriflock Dalam Menurunkan Kadar TSS, Besi Dan Mangan Pada Air Tambang Di Settling Pond PT.Adaro Indonesia - Ahmad Tantowy; Syarifudin A; Abdul Haris (Jurnal Sains Farmasi Dan Kesehatan, 2024)
The Effectiveness of the Use of Kuriflock in Reducing TSS, Iron and Manganese Levels in Mining Water in Settling Pond PT. Adaro Indonesia. PT. Adaro Indonesia is the largest coal miner of the Adaro Group, which produces coal products. Coal mining carried out by the open-pit mining method causes negative impacts on the environment, one of which is the emergence of waste in the form of mining water. The general purpose of this study is to determine the effectiveness of the use of Kuriflock in reducing TSS, iron (Fe) and manganese (Mn) in the Settling Ponds Disposal Area of PT. Adaro Indonesia before being released into the Public Waters Agency.The type of research used is experimental research. The research design used was Pretest-Postest with Control Group Design. The sample in this study was taken using the Grab Sampling method taken on the catchmen from the runoff of PT. Buma. In this study, 4 concentrations of 0 mg/l, 0.2 mg/l, 0.4 mg/l and 0.6 mg/l were used with 5 repetitions. The results of this study show that curiflock cannot reduce the levels of TSS, Iron (Fe) and Manganese (Mn). The levels of TSS and Iron (Fe) before and after being certified have not met the standard value of ligkungan quality. Meanwhile, the level of Manganese (Mn) has met the quality standard value. It is necessary to use other coagulants to reduce the levels of TSS, Iron (Fe) and Manganese (Mn) in mine water (Disposal Area) in accordance with environmental quality standards.